Estudio Del Liderazgo Estudiantil Desde Las Motivaciones Para Su ElecciÃ³n. El Caso De La Universidad De Santo TomÃ¡s De Bucaramanga (Colombia) - GÃ³mez, Miguel LÃ³pez; RodrÃguez-GarcÃa, Antonio-Manuel; Montoro, Miriam Ãgreda (European Scientific Journal, ESJ, 2016)
This paper shows an investigation developed at the University of Santo TomÃ¡s (Bucaramanga) about the qualities that students consider important to practice the student leadership. For that reason, an ad hoc questionnaire with a reliability index of 0,814 has been designed. The sample consisted of 38 students (55% male and 45% female) from different degrees. The results show values such as charisma, commitment, consistency, fidelity, honesty, loyalty, frankness, sincerity and firmness of the person as the most important qualities that the student must have to be chosen as a representative of students.